Chapter 17 Atomized Solidarity and New Shapes of Resistance Visual Activism in South Africa after Apartheid - Thomas, Kylie (Taylor & Francis, 2023)
This chapter provides a concise history of visual activism in South Africa and focuses on how contemporary artists and activists make use of visual forms to intervene in public space, to document injustice, and to express dissent. The chapter argues that visual activism is best understood as a call to those who look to move from seeing and knowing to acting. Through analyses of works by visual activists Zanele Muholi, Haroon Gunn-Salie, and the Tokolos Stencils Collective, and through engaging with a campaign created by the social justice movement Section27, the essay shows how such work draws attention to homophobia and sexual violence; impunity for crimes against humanity; and ongoing inequality in the aftermath of apartheid. The essay also considers what occurs when visual activist works are detached from collective mobilizing and circulate within the neo-liberal art economy, producing forms of atomized solidarity.